The external game demands of professional, male basketball players according to playing position and playing role: a multiseason analysis in the Australian national basketball league - Shirley, S. K.; Scanlan, A. T.; Guy, J. H.; Bartlett, R. J.; Bowe, S. J.; Elsworthy, N. (The Journal of Strength and Conditioning Research, 2026)
This observational study provides a contemporary and novel analysis of the external game demands experienced by professional, male basketball players competing in the Australian National Basketball League (NBL) and compares these demands between playing roles and playing positions. Twenty-two professional, male basketball players (age: 27.0 ± 3.3 years) were monitored over 2 competitive seasons between 2021 and 2023 using microsensor technology (T6; Catapult Sports). Players were categorized according to playing role (starting, bench) and playing position (frontcourt, backcourt). Accumulated (total) and relative (per minute) external game demands were calculated for PlayerLoad in addition to total and high-intensity inertial movement analysis variables during live playing time. External game demands were quantified as estimated marginal means (95% confidence limits) and compared between playing roles and playing positions via linear mixed model and Cohen's d effect size analyses. Significance was set at p <= 0.05. Starting players experienced higher accumulated external game demands than bench players across most variables (p < 0.05, d = 0.30-1.87), whereas relative external game demands were similar between playing roles (p > 0.05, d = 0.01-0.44). Likewise, external game demands were comparable between playing positions across variables (p > 0.05, d = 0.03-1.15). These findings demonstrate that only accumulated external game demands differ between playing roles, whereas homogeneity in external game demands appear to exist between generalized playing positions. These foundation data in the Australian NBL may inform training and recovery protocols among end-users working in this competition to ensure players are optimally prepared for competition according to their specific requirements.